TRANSFORMATION IN THE REGIME IN UZBEKISTAN: TAGES AND OUTCOME - BORISOV, Nikolai (CENTRAL ASIA AND THE CAUCASUS, 2005)
Researchers are showing a great interest in the political changes occurring in the post-Soviet countries. This is because these changes have led to the creation of absolutely different political regimes which at times are even totally opposite to each other in their nature and content. This has not only given experts much food for thought regarding the factors prompting the formation of these regimes, the reasons for their differences and the possibilities of further changes, but has also given rise to the need for reconsidering the traditional transitological approaches which view political transformation as the democratization and modernization of the political system of a particular state. The most important presuppositions from which our analysis of the current situation proceeds are based, first, on the hypothesis that the transformation process and the existence of so-called “paths of dependence” are historically determined; and second, on the hypothesis that the regime which formed in Uzbekistan differs in several key characteristics from Soviet power, being more akin to the pre-Soviet regimes of the Central Asian khanates.